Approaching the Knee with Direct Measurements - S. L. Nutter; Gabriele Bigongiari; Arturo Alejandro Menchaca-Rocha; A. Malinin; P. J. Boyle; Riccardo Zei; J. J. Beatty; L. Derome; M. H. Lee; H. S. Ahn; Maria Grazia Bagliesi; Y. S. Yoon; et al. (Nuclear Physics B - Proceedings Supplements, 2008)
The Cosmic Ray Energetics And Mass (CREAM) experiment was designed and constructed to push spectral measurements of individual cosmic-ray nuclei from H to Fe to energies approaching the "knee" in a series of balloon flights. A cumulative exposure of 70 days was achieved during two circumpolar flights in Antarctica in 2005 and 2006. Direct measurements at the top of the atmosphere allow event-by-event determination of the incident cosmic-ray particle charge and energy. The objective is to investigate whether and how the knee structure is related to the mechanisms of particle acceleration, propagation, and confinement. The recovered payload is being refurbished for its third flight, which is scheduled for launch in December 2007. The combination of sophisticated particle detectors and long duration balloon flight capabilities now promise high quality measurements over an energy range that was not previously accessible.